Nano chelating blocking remover as well as preparation method, use method and application thereof

Through the use of nano-chelating deblocking agent, the problem of efficient treatment of complex blockages in oil and gas fields is solved, and the blockage of polymer micelles, inorganic scales, and clay minerals is achieved in a single step, which improves the production efficiency and environmental friendliness of oil wells.

CN119193129APending Publication Date: 2024-12-27CHINA OILFIELD SERVICES LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411335366.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Prior Art When treating complex blockages formed by polymeric micelles, inorganic scales and clay minerals in oil and gas fields, the multi-stage injection treatment time is long, the fluid volume is large, and the blocking effect is poor, and the deposited scale may be pushed into the storage. Deep in the layer, increasing the difficulty of subsequent processing.

Method used

Provide a nano-chelation deblocking agent, containing the chelating agent aqueous phase, oil phase, surfactant and cosurfactant, and forms a nanostructure through mixing and stirring, with O/W type uniform dispersion system, ultra-low interfacial tension, can Effectively dissolve and degrade polymeric micelles, inorganic scales and clay minerals to form a single-step solution to remove complex blockages.

Benefits of technology

It has achieved efficient cleaning of heavy components in crude oil, with dissolution and degradation rates reaching 80% or more, dissolved inorganic scale by 95% or more, viscosity reduction rate by 90% or more, and demulsification rate by 90% or more, and is not Acid, safe and environmentally friendly, reduces corrosion and simplifies the treatment process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119193129A_ABST
    Figure CN119193129A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of oil-gas field development and exploitation, and particularly relates to a nano chelating blocking remover as well as a preparation method, a use method and application thereof. The nano chelating blocking remover provided by the invention comprises the following components in percentage by weight: 60%-95% of a chelating agent-containing water phase, 0.1%-10% of an oil phase, 0.1%-20% of a surfactant and 0.1%-10% of a cosurfactant. The nano chelating blocking remover provided by the invention is an O / W type nano homogeneous dispersion system, the particle size is distributed within the range of 8-100nm, and complex blocking caused by polymer micelles, inorganic scales, clay minerals, crude oil and mixtures thereof can be effectively removed in a single step.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil and gas field development and exploitation, and specifically relates to a nano chelating plugging remover and a preparation method, a use method and an application thereof. Background Art

[0002] The blockage in the near-wellbore area seriously affects the normal production of oil and gas. The pollutants in oil and water wells can be divided into organic sediment scale and inorganic sediment scale. Organic sediments are mainly paraffin, asphaltene and injected polymer components in crude oil. Due to the change of phase equilibrium in multiphase flow or the injection of incompatible systems such as solvents, gases, and acids in reservoir transformation measures, the composition of crude oil is changed, thereby causing the precipitation of heavy components. Inorganic sediments are mainly caused by the corrosion of pipelines and equipment, which gradually oxidizes iron ions and forms ferric hydroxide and ferrous hydroxide precipitation. In addition, the mineralization of formation water is high, and inorganic scales such as calcium, magnesium, barium, and strontium will be produced during the development and production process. For polymer injection wells, polymer injection effect wells, and profile control and drive wells, polyacrylamide and its derivatives are cross-linked with high-valent metal cations to form polymer micelles, and entrain, entrap, and adhere to crude oil, inorganic scale and clay minerals to form complex blockages.

[0003] Chinese invention patent CN117735737A discloses a novel chelating descaling agent for declogging calcium carbonate scale and barium sulfate scale and a preparation method thereof. The descaling agent of the invention is neutral or weakly alkaline and can quickly dissolve calcium carbonate scale and barium sulfate scale under certain conditions; at the same time, it will not corrode the surface of metal and plastic equipment; and it has good dispersibility and will not clog pipelines; it is biodegradable and environmentally friendly; the system does not have the performance of dissolving mixed blockages such as polymer micelles, clay minerals, and crude oil. Chinese invention patent CN117511527B discloses a descaling and unblocking agent and its preparation method. The azacrown ether chelating agent of the invention contains azacrown ether chelating groups, which have strong coordination bonds with barium ions and can form stable coordination chelates. The azacrown ether chelating agent contains carboxyl, hydroxyl, sulfonic acid and other groups, which can further improve the chelating ability with barium ions, effectively inhibit the crystallization of barium ions and the formation of precipitated scale, and has excellent dissolution rate for barium sulfate polymers, showing excellent unblocking performance; the system does not have the performance of dissolving mixed blockages such as polymer micelles, clay minerals, and crude oil. Chinese invention patent CN117683524A discloses an oilfield unblocking agent and unblocking method. The invention patent shows that the oilfield unblocking agent system integrated with oil washing, oil displacement, and acidification is made of mixed benzene, polybasic organic acid and non-ionic surfactant, chelating agent, alcohol, etc., which has the advantage of strong dissolution ability of oil-based cores; the system does not have the performance of dissolving mixed blockages such as polymer micelles, clay minerals, and crude oil.

[0004] At present, the best way to deal with organic scale such as asphaltene and paraffin in industry is to inject chemical reagents composed of aromatic mixed solvents and auxiliary solvents. For polymer micelles, oxidative depolymerization agents are often used for treatment. For inorganic scale and clay minerals, acidification and chelation treatment are the most commonly used methods. In view of the complex blockage formed by polymer micelles, crude oil, inorganic scale and clay minerals, the multi-stage injection method of organic solvent + depolymerization agent + acid solution is often used on site for treatment. In multi-stage injection treatment, the cleaning time is long and the fluid volume is large, which seriously affects the economic benefits of the project. In addition, the injected single-effect treatment fluid may push the untreatable deposited scale into the deep part of the reservoir, deepening the difficulty of subsequent treatment; and the complex blockage formed by polymer micelles, crude oil, inorganic scale and clay minerals has a complex structure, which leads to a significant reduction in the dissolution efficiency of the multi-stage injection agent and poor deblocking effect. Summary of the invention

[0005] In view of the defects of the prior art, the present invention provides a nano-chelating plugging remover and a preparation method, a use method and an application thereof.

[0006] Specifically, the nano-chelating plugging remover provided by the present invention comprises, by weight percentage: 60%-95% of a chelating agent-containing aqueous phase, 0.1%-10% of an oil phase, 0.1%-20% of a surfactant and 0.1%-10% of a co-surfactant.

[0007] The nano-chelating plugging remover comprises, by weight percentage, 80%-90% of a chelating agent-containing aqueous phase, 1%-4% of an oil phase, 6%-10% of a surfactant and 3%-6% of an auxiliary surfactant.

[0008] The nano-chelating plugging remover comprises, by weight percentage, 86% of a chelating agent-containing aqueous phase, 2% of an oil phase, 8% of a surfactant and 4% of an auxiliary surfactant.

[0009] The nano-chelating plugging remover mentioned above, the chelating agent-containing aqueous phase comprises the chelating agent, the demulsifier and water in a weight ratio of (10-30): (0.1-2.0): (59-89.9).

[0010] The above-mentioned nano-chelating plugging remover, the chelating agent is selected from two or more of sodium citrate, trisodium nitrilotriacetate, trisodium hydroxyethylethylenediaminetriacetate, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, tetrasodium aminotrimethylene phosphate, tetrasodium hydroxyethylidene diphosphate, pentasodium diethylenetriaminepentamethylenediphosphate, pentasodium diethylenetriaminepentaacetate and tetrasodium glutamate diacetate; the demulsifier is selected from one or more of sodium dioctyl diacid sulfonate, polyoxyethylene ether, phenolamine resin polyether, phenolic resin polyether and polyacrylate.

[0011] In the above-mentioned nano-chelating plugging remover, the oil phase is selected from one or more of n-hexane, cyclohexane, limonene, and high-flash-point heavy aromatic hydrocarbons.

[0012] The above-mentioned nano-chelating plugging remover, the surfactant is one or more of dodecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, fatty alcohol polyoxyethylene ether, sodium dodecyl sulfate, and styrylphenol polyoxyethylene ether.

[0013] In the above-mentioned nano-chelating plugging remover, the co-surfactant is one or more of isopropanol, n-butanol, n-pentanol, n-hexanol, ethylene glycol, and propylene glycol.

[0014] The nano-chelate plugging remover comprises: mixing a chelate-containing water phase, an oil phase, a surfactant and a co-surfactant in proportion, and stirring at 0-50° C. for 0.5-2 hours to obtain the nano-chelate plugging remover.

[0015] On the other hand, the present invention also provides a method for using the above-mentioned nano-chelating plugging remover, comprising:

[0016] (1) Injecting nano-chelated plugging remover into the well;

[0017] (2) injecting displacement fluid;

[0018] (3) After shutting in the well for 6-48 hours, the oil well is put into production / the water well is put into operation.

[0019] The method for using the above-mentioned nano-chelate plugging remover, in step (1), the displacement of the nano-chelate plugging remover is 0.1-1.5m 3 / min; in step (2), the displacement of the displacement fluid is 0.1-1.5m 3 / min.

[0020] In another aspect, the present invention also provides the use of the above-mentioned nano-chelated plugging remover in the development and exploitation of sandstone and carbonate oil and gas reservoirs.

[0021] The technical solution of the present invention has the following beneficial effects:

[0022] (1) The nano-chelate plugging remover of the present invention is an O / W type nano-uniformly dispersed system, in which oil and water are mutually soluble and intercommunicable, and has an ultra-low interfacial tension of 10 -3 Below mN / m;

[0023] (2) The nano-chelated plugging remover of the present invention can effectively clean crude oil and dissolve heavy components in crude oil, with an oil washing efficiency of more than 80% and an asphalt dissolution rate of more than 10%;

[0024] (3) The nano-chelating plugging remover of the present invention can effectively degrade polymer micelles, with a viscosity reduction rate of more than 90%;

[0025] (4) The nano-chelated plugging remover of the present invention can effectively dissolve inorganic scale, with a dissolution rate of more than 95% for ferric hydroxide, ferrous hydroxide, calcium carbonate, calcium sulfate, and magnesium carbonate, and a dissolution rate of more than 90% for barium sulfate and strontium sulfate;

[0026] (5) The nano-chelated plugging remover of the present invention can dissolve some clay minerals, and the dissolution rate of kaolinite, illite, montmorillonite and chlorite is more than 10%;

[0027] (6) The nano-chelate plugging remover of the present invention is non-acidic, safe and environmentally friendly, and has low corrosiveness. The corrosion rate at 140°C is less than 0.1 g / m 2 h or less;

[0028] (7) The nano-chelate plugging remover of the present invention also has the performance of demulsification, and the demulsification rate is above 90%;

[0029] (8) The nano-chelating plugging remover provided by the present invention is an O / W type nano-homogeneous dispersion system with a particle size distribution in the range of 8 to 100 nm. It can effectively remove complex blockages caused by polymer micelles, inorganic scale, clay minerals, crude oil and mixtures thereof in a single step. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Various other advantages and benefits will become apparent to those of ordinary skill in the art by reading the following detailed description of the preferred embodiment.The drawings are only for the purpose of illustrating the preferred embodiments and are not to be construed as limiting the invention.

[0031] Figure 1 The appearance of the nano-chelating plugging remover of the present invention;

[0032] Figure 2 This is the appearance of the 1# mixed plugging sample;

[0033] Figure 3 This is the appearance of the 2# mixed plugging sample;

[0034] Figure 4 This is the on-site construction curve of X-1 well;

[0035] Figure 5 This is the on-site construction curve of X-2 well. DETAILED DESCRIPTION

[0036] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific embodiments. Except for the following contents, the process method of the present invention adopts conventional methods or devices in the art. Unless otherwise specified, the following terms have the meanings commonly understood by those skilled in the art.

[0037] When a numerical range is disclosed herein, the above range is considered to be continuous and includes the minimum and maximum values ​​of the range, as well as every value between such minimum and maximum values. Further, when a range refers to an integer, every integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe a feature or characteristic, the ranges can be combined. In other words, unless otherwise indicated, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0038] Specifically, in a first aspect, the present invention provides a nano-chelating plugging remover, comprising a chelating agent-containing aqueous phase, an oil phase, a surfactant and a co-surfactant.

[0039] A chelating plugging remover with a nanostructure can be prepared from a chelating agent-containing water phase, an oil phase, a surfactant and a co-surfactant. Due to its special nanostructure and oil-water miscible and interoperable structure, it can give full play to the synergistic effect of the chelating agent and the solvent oil, and efficiently remove complex blockages caused by polymers, inorganic scales, clay minerals, crude oil and their mixtures in a single step.

[0040] The following is a detailed description of the components of the nano-chelate plugging remover of the present invention:

[0041] Chelating agent aqueous phase

[0042] The chelating agent-containing aqueous phase extracts metal ions (calcium, magnesium, barium, strontium and other metal ions) in the clay lattice by chelation, forming nano-sized soluble oxygen clusters, destroying the clay lattice and dissolving clay minerals.

[0043] The chelating agent-containing aqueous phase comprises a chelating agent, a demulsifier and water in a weight ratio of (10-30): (0.1-2.0): (59-89.9).

[0044] In some preferred embodiments, the chelating agent is selected from two or more of sodium citrate, trisodium nitrilotriacetate, trisodium hydroxyethylethylenediaminetriacetate, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, tetrasodium aminotrimethylene phosphate, tetrasodium hydroxyethylidene diphosphate, pentasodium diethylenetriamine pentamethylidene acid, pentasodium diethylenetriamine pentaacetate and tetrasodium glutamate diacetate.

[0045] The present invention captures metal ions in polymer micelles by using the chelating agent with the special structure, masks the metal ions in the polymer micelles, thereby destroying the cross-linked structure of the polymer molecules, degrading the polymer micelles and reducing their viscosity.

[0046] In some preferred embodiments, the demulsifier is selected from one or more of sodium dioctyl sulfonate, polyoxyethylene ether, phenolamine resin polyether, phenolic resin polyether, and polyacrylate.

[0047] Demulsifiers are used to prevent crude oil from emulsifying and improve the permeability of fluids in rocks.

[0048] In some preferred embodiments, the content of the chelating agent-containing aqueous phase in the nano-chelating plugging remover of the present invention is 60%-95% by weight.

[0049] When the proportion of the aqueous phase containing the chelating agent is too high, the oil phase content decreases accordingly, and the ability to clean crude oil and dissolve heavy components in crude oil is limited; when the proportion of the aqueous phase containing the chelating agent is low, the ability to remove polymer micelles, clay minerals and inorganic scale is reduced.

[0050] Further preferably, the content of the chelating agent-containing aqueous phase in the nano-chelating plugging remover is 80%-90% by weight.

[0051] More preferably, the content of the chelating agent-containing aqueous phase in the nano-chelating plugging remover is 86% by weight.

[0052] oil phase

[0053] The oil phase can effectively dissolve heavy components such as paraffin and asphaltene in crude oil.

[0054] In some preferred embodiments, the oil phase is selected from one or more of n-hexane, cyclohexane, limonene, and high flash point heavy aromatic hydrocarbons.

[0055] In some preferred embodiments, the content of the oil phase in the nano-chelating plugging remover of the present invention is 0.1%-10% by weight.

[0056] Practice has shown that when the oil phase content is too high, it will affect the stability of the nano-chelating plugging remover structure; when the oil phase content is too low, the ability to clean crude oil and dissolve heavy components in crude oil is limited.

[0057] Further preferably, the content of the oil phase in the nano-chelating plugging remover is 1%-4% by weight.

[0058] More preferably, the content of the oil phase in the nano-chelating plugging remover is 2% by weight.

[0059] Surfactants

[0060] The surfactant is used to form a nanostructured chelating deblocking agent and reduce the surface tension of the liquid.

[0061] In some preferred embodiments, the surfactant is one or more of dodecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, fatty alcohol polyoxyethylene ether, sodium dodecyl sulfate, and styrylphenol polyoxyethylene ether.

[0062] In some preferred embodiments, the content of surfactant in the nano-chelating plugging remover of the present invention is 0.1%-20% by weight.

[0063] When the surfactant content is too low, a nano-chelated plugging remover with a stable structure cannot be formed; when the surfactant content is too high, the viscosity is too high, making preparation and use difficult.

[0064] Further preferably, the content of the surfactant in the nano-chelating plugging remover is 6%-10% by weight.

[0065] More preferably, the content of the surfactant in the nano-chelating plugging remover is 8% by weight.

[0066] Co-surfactant

[0067] The co-surfactant is used to assist the surfactant in forming a nanostructured chelating plugging remover.

[0068] In some preferred embodiments, the co-surfactant is one or more of isopropanol, n-butanol, n-pentanol, n-hexanol, ethylene glycol, and propylene glycol.

[0069] In some preferred embodiments, the content of the co-surfactant in the nano-chelating plugging remover of the present invention is 0.1%-10% by weight.

[0070] Practice has shown that when the content of the co-surfactant is too little, the viscosity is too high, making preparation and use difficult; when the content of the co-surfactant is too high, it is difficult to form a nano-chelating plugging remover with a stable structure.

[0071] Further preferably, the content of the co-surfactant in the nano-chelating plugging remover is 3%-6% by weight.

[0072] More preferably, the content of the co-surfactant in the nano-chelating plugging remover is 4% by weight.

[0073] In a second aspect, the present invention provides a method for preparing the above-mentioned nano-chelating plugging remover, comprising: mixing a chelating agent-containing aqueous phase, an oil phase, a surfactant and a co-surfactant in proportion, and stirring at 0-50° C. for 0.5-2 hours to obtain the nano-chelating plugging remover.

[0074] The preparation method of the nano-chelating plugging remover of the present invention is simple in preparation, convenient in on-site operation, and free of flowback, and has great significance for the development and exploitation of oil and gas fields.

[0075] In a third aspect, the present invention provides a method for using the above-mentioned nano-chelating plugging remover, comprising:

[0076] (1) Injecting nano-chelated plugging remover into the well;

[0077] (2) injecting displacement fluid;

[0078] (3) After shutting in the well for 6-48 hours, the oil well is put into production / the water well is put into operation.

[0079] The nano-chelating plugging remover of the present invention has a simple use method and can effectively remove complex blockages caused by polymer micelles, inorganic scale, clay minerals, crude oil and mixtures thereof in a single step.

[0080] Among them, the polymer micelle is a water-insoluble micelle formed by cross-linking polyacrylamide and its derivatives with high-valent metal cations, the inorganic scale is one or more of ferric hydroxide, ferrous hydroxide, calcium carbonate, calcium sulfate, magnesium carbonate, barium sulfate, and strontium sulfate, the clay mineral is one or more of kaolinite, illite, montmorillonite, and chlorite, and the crude oil is crude oil containing a certain amount of heavy components such as paraffin and asphaltene; the mixture is two or more of the polymer, inorganic scale, clay mineral, and crude oil.

[0081] In some preferred embodiments, the displacement of the nano-chelating plugging remover is 0.1-1.5 m 3 / min, the displacement of the displacement fluid is 0.1-1.5m 3 / min.

[0082] In a fourth aspect, the present invention also provides the use of the above-mentioned nano-chelated plugging remover in the development and exploitation of sandstone and carbonate oil and gas reservoirs.

[0083] The nano-chelate plugging remover of the present invention utilizes a special oil-water miscible and intercommunication structure, and can effectively remove complex blockages caused by polymers, inorganic scales, clay minerals, crude oil and mixtures thereof in a single step. In addition, the nano-chelate plugging remover of the present invention is non-acidic (pH is greater than or equal to 7), safe and environmentally friendly (low toxicity, low corrosiveness), simple to prepare (can be prepared in an on-site mud pool), easy to operate on-site, and free of backflow (the backflow fluid does not need to be treated and can be directly introduced into the production process), which is of great significance for the development and exploitation of oil and gas fields.

[0084] Example

[0085] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions. The raw materials used in the following examples are all conventionally purchased.

[0086] Example 1

[0087] Preparation of the first liquid: In a ceramic reactor, add 2g of high flash point heavy aromatic hydrocarbon (S150 solvent oil, Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.), 4g of isopropanol, 4g of fatty alcohol polyoxyethylene ether (MOA-7, Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.), 2g of styrylphenol polyoxyethylene ether (Nongru 600, Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.), and 2g of tetradecyltrimethylammonium bromide;

[0088] Preparation of the second liquid: In a ceramic reactor, add 5 g of disodium ethylenediaminetetraacetate, 5 g of tetrasodium ethylenediaminetetraacetate, 10 g of tetrasodium hydroxyethylidene diphosphate, 1 g of sodium dioctyl diacid sulfonate and 65 g of water.

[0089] Compounding: Seal the reactor and continue stirring. When the reactor is heated to 50°C by steam, the reaction temperature is controlled at about 50°C by the automatic control system. The pressure in the reactor does not need to be controlled and does not exceed 1.0MPa. After 1 hour, when the dissolution is complete, cool it with circulating water. When the temperature is below 30°C, discharge it from the bottom of the reactor to obtain 100g of nano-chelate plugging remover. The appearance of nano-chelate plugging remover is shown in Figure 1 , uniform and transparent, with no scattering phenomenon under the irradiation of infrared laser pen.

[0090] 1# mixed plug sample: sampled from X-1 well in Bohai Oilfield, composed of 22.7% crude oil, 7.7% polymer, 35.3% inorganic minerals and 24.3% water. Among them, the content of colloid and asphalt in crude oil accounts for 28.1%; the polymer is polyacrylamide; the inorganic minerals are composed of 24% calcium carbonate, 18% magnesium carbonate, 44% iron hydroxide and 14% clay minerals. The appearance of 1# mixed plug sample is shown in Figure 2 , it has a very high viscosity, cannot flow, and has a certain elasticity.

[0091] Asphalt dissolution rate determination method:

[0092] 1) Weigh the N80 steel sheet and record m1, accurate to 0.001g (the size of the steel sheet shall be in accordance with the provisions of Section 4.1.2 of the coupon size of "SY / T 5405-2019 Test Methods and Evaluation Indicators for Acidification Corrosion Inhibitors");

[0093] 2) Soak the steel sheet (below the hole end) evenly in the pre-heated asphalt (10# asphalt), dip about 2g of asphalt, weigh and record m2, accurate to 0.001g; set aside;

[0094] 4) Take 200 mL of nano-chelated plugging remover and place the asphalt hanging piece in the lower middle part of the thread-mouth bottle;

[0095] 5) Place the experimental thread-mouth bottle in a 90°C water bath for 24 hours, then take out the hanging piece and record the weight m3 of the hanging piece taken out, accurate to 0.001g;

[0096] The asphalt dissolution rate is x1 and is calculated as follows:

[0097] x1=(m3-m2) / (m2-m1)*100%

[0098] Where:

[0099] x1——soluble asphalt rate, %;

[0100] m1——the mass of N80 steel sheet, g;

[0101] m2——mass of N80 steel sheet coated with asphalt, g;

[0102] m3——The mass of N80 steel sheet after immersion, g

[0103] The arithmetic mean of the test results of two parallel experiments was taken as the measurement result.

[0104] Determination method of soluble calcium carbonate rate / soluble magnesium carbonate rate / soluble iron hydroxide rate / soluble clay mineral rate:

[0105] 1) Place the sample in a constant temperature drying oven, dry it, and place it in a desiccator to cool it for later use;

[0106] 2) Dry the filter paper to a constant weight, weigh it and record it as m1;

[0107] 3) preparing nano-chelating plugging remover according to the formula;

[0108] 4) Weigh 2.0 g of sample, accurate to 0.001 g, record as m, add 40 mL of nano-chelating plugging remover, keep constant temperature in a 90°C water bath, and react for 24 hours.

[0109] 5) Filter with constant weight filter paper, then dry the filter paper to constant weight, weigh it, and record it as m2. Use the above method to conduct two sets of parallel experiments;

[0110] 6) Calculate the dissolution rate

[0111] x2=(m1+m-m2) / m*100%

[0112] Where:

[0113] x2—dissolution rate of the sample by the solution, %;

[0114] m1—pre-treated filter paper weight, g;

[0115] m2—weight of the sample after filtering the acid solution and drying with the filter paper to constant weight, g;

[0116] m—Weigh the weight of the sample, g.

[0117] Determination of viscosity reduction

[0118] 1) Determination of sample apparent viscosity

[0119] Take 400 ml of the sample and place it in a 500 ml beaker. Add 40 ml of fresh water to the sample and stir with a glass rod to mix it evenly. Seal it and put it in an oven at 90°C for 24 hours. Take it out and cool it to room temperature. Determine the apparent viscosity of the sample according to the provisions of 6.3 of GB / T16783.1-2014.

[0120] 2) Determination of apparent viscosity of samples with nano-chelating plugging remover

[0121] Take another 400ml sample and place it in a 500ml beaker, add 40ml of nano-chelating plugging remover to the sample, stir with a glass rod to mix it evenly, seal it and put it in an oven, place it at 90℃ for 24h, take it out, cool it to room temperature, and measure the apparent viscosity of the sample according to the provisions of 6.3 in GB / T 16783.1-2014. Calculate the viscosity reduction rate according to the following formula:

[0122] P=(AV0-AV1) / AV0*100%

[0123] Where:

[0124] P——viscosity reduction rate, %;

[0125] AV0——apparent viscosity of the sample without adding nano-chelating plugging remover, mPa·s;

[0126] AV1——Apparent viscosity of the sample with nano-chelating plugging remover, mPa·s.

[0127] Demulsification rate determination method:

[0128] 1) Take 50mL of dehydrated crude oil (properties of crude oil: density ≥ 0.915g / cm 3 ; Viscosity ≥ 300mPa·s) and 50mL of nano-chelating plugging agent are placed in a dehydration bottle. After tightening the bottle cap, the dehydration bottle is quickly placed on an electric shaker and shaken for 0.5-5min to fully mix.

[0129] 2) Remove the dehydration test bottle, loosen the bottle cap, and quickly place the dehydration bottle in a 90℃ constant temperature water bath to let it settle for 2 hours. Observe the demulsification and water separation, and read the water phase volume V 出水 .

[0130] The demulsification rate DE (i.e. dehydration rate) is calculated according to the following formula, and the integer digit must be retained during the calculation.

[0131] DE=V 出水 / V 水 *100%

[0132] Where: DE——demulsification rate, %;

[0133] V 出水 ——dehydrated volume, mL;

[0134] V 水 ——The volume of water in the emulsion, mL.

[0135] The arithmetic mean of the two sets of parallel determination results was taken as the determination result, and the relative deviation of the two parallel determination results was less than 10%.

[0136] The interfacial tension determination method shall be carried out in accordance with the rotating drop method specified in 6.3.6 of "SY / T 5755-2016 Performance Evaluation Method of Exhaust Aids for Fracturing Acidification".

[0137] Table 1 Performance test results of nano-chelating plugging remover

[0138]

[0139]

[0140] Well X-1 is an oil production well in Bohai Oilfield. It cannot produce normally due to blockage in the area near the well. The reasons for the blockage of the well are complicated. Conventional positive squeeze, backwash, annular fluid replenishment trial production, and conventional gel breaking measures cannot solve the problem. The nano-chelate plugging remover of Example 1 was used to unblock the well. The amount of nano-chelate plugging remover was 30 tons. After unblocking, the well was shut down for 24 hours. After resuming production, the oil production of the well reached 70m 3 / d, which shows that the nano-chelated plugging-removing liquid of this embodiment can well solve the complex plugging problems caused by polymer micelles, inorganic scale, clay minerals, crude oil and their mixtures, and ensure the normal production of oil wells. Figure 4 It can be seen that with the injection of nano plugging agent, the construction displacement gradually increased from 0.43m 3 / min increased to 0.66m 3 / min, the construction pressure was reduced from 9.6MPa to 6.8MPa, and the unblocking effect was significant.

[0141] Example 2

[0142] Preparation of the first liquid: In a ceramic reactor, add 1g of high flash point heavy aromatic hydrocarbon (S150 solvent oil, Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.), 1g of cyclohexane, 4g of isopropanol, 4g of fatty alcohol polyoxyethylene ether (MOA-7, Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.), 2g of styrylphenol polyoxyethylene ether (Nongru 600, Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.), and 2g of tetradecyltrimethylammonium bromide;

[0143] Preparation of the second liquid: In a ceramic reactor, add 5 g of disodium ethylenediaminetetraacetate, 5 g of tetrasodium ethylenediaminetetraacetate, 10 g of pentasodium diethylenetriaminepentaacetate, 1 g of sodium dioctyl sulfonate and 65 g of water.

[0144] Compounding: Seal the reactor and continue stirring. When it is heated to 50°C by steam, the reaction temperature is controlled at about 50°C by the automatic control system. The pressure in the reactor does not need to be controlled and does not exceed 1.0MPa. After 1 hour, when the solution is complete, pass circulating water for cooling. When the temperature drops below 30°C, discharge it from the bottom of the reactor to obtain 100g of nano-chelating plugging remover.

[0145] 2# mixed plugging sample: sampled on-site at X-2 well in the South China Sea Oilfield, consisting of 28.9% crude oil, 16.3% calcium carbonate, 28.3% iron hydroxide, 9.2% barium sulfate, 4.8% strontium sulfate, 7.2% clay minerals and 5.3% water. Among them, the content of colloid and asphalt in crude oil accounts for 49.8%. The appearance of 2# mixed plugging sample is shown in Figure 3 .

[0146] The experimental method and experimental steps are the same as those in Example 1.

[0147] Table 2 Performance test results of nano-chelating plugging remover

[0148]

[0149]

[0150] Well X-2 is an oil production well in the South China Sea Oilfield. It cannot produce normally due to blockage in the area near the well. The reasons for the blockage of the well are complex, and conventional unblocking measures cannot solve the problem. The nano-chelate unblocking agent of Example 2 was used to unblock the well. The amount of nano-chelate unblocking liquid used was 30 tons. After unblocking, the well was shut down for 24 hours. After resuming production, the oil production of the well reached 40m 3 / d, which shows that the nano-chelated plugging-removing liquid of this embodiment can well solve the complex plugging problems caused by complex inorganic scale, clay minerals, crude oil and their mixtures, and ensure the normal production of oil wells. Figure 5 It can be seen that with the injection of nano plugging agent, the construction displacement is maintained at 0.95m 3 / min, the construction pressure was reduced from 9.8MPa to 7.9MPa, and the unblocking effect was significant.

[0151] Example 3

[0152] Preparation of the first liquid: in a ceramic reactor, add 4 g of cyclohexane, 6 g of isopropanol, 5 g of fatty alcohol polyoxyethylene ether (MOA-7, Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.), 2.5 g of styrylphenol polyoxyethylene ether (Nongru 600, Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.), and 2.5 g of tetradecyltrimethylammonium bromide;

[0153] Preparation of the second liquid: In a ceramic reaction kettle, add 5 g of disodium ethylenediaminetetraacetate, 15 g of trisodium hydroxyethylethylenediaminetriacetate, 1 g of sodium dioctyl sulfonate and 59 g of water.

[0154] Compounding: Seal the reactor and continue stirring. When it is heated to 50°C by steam, the reaction temperature is controlled at about 50°C by the automatic control system. The pressure in the reactor does not need to be controlled and does not exceed 1.0MPa. After 1 hour, when the solution is complete, pass circulating water for cooling. When the temperature drops below 30°C, discharge it from the bottom of the reactor to obtain 100g of nano-chelating plugging remover.

[0155] Table 3 Performance test results of nano-chelating plugging remover

[0156]

[0157]

[0158] Example 4

[0159] Preparation of the first liquid: In a ceramic reactor, add 1 g of cyclohexane, 3 g of isopropanol, 3 g of fatty alcohol polyoxyethylene ether (MOA-7, Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.), 1.5 g of styrylphenol polyoxyethylene ether (Nongru 600, Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.), and 1.5 g of tetradecyltrimethylammonium bromide;

[0160] Preparation of the second liquid: In a ceramic reaction kettle, add 4g of disodium ethylenediaminetetraacetate, 4g of tetrasodium ethylenediaminetetraacetate, 15g of trisodium hydroxyethylethylenediaminetriacetate, 1g of sodium dioctyl diacid sulfonate and 66g of water.

[0161] Compounding: Seal the reactor and continue stirring. When it is heated to 50°C by steam, the reaction temperature is controlled at about 50°C by the automatic control system. The pressure in the reactor does not need to be controlled and does not exceed 1.0MPa. After 1 hour, when the solution is complete, pass circulating water for cooling. When the temperature drops below 30°C, discharge it from the bottom of the reactor to obtain 100g of nano-chelating plugging remover.

[0162] Table 4 Performance test results of nano-chelating plugging remover

[0163] Performance Indicators Measurement data Asphalt dissolving rate 10.5% Calcium carbonate dissolution rate 100% Solubility of iron hydroxide 100% Barium sulfate dissolution rate 92.5% Strontium sulfate dissolution rate 91.5% Dissolved clay mineral rate 16% Demulsification rate 98% Interfacial tension 0

[0164] Comparative Example 1: High Flash Point Aromatic Hydrocarbons

[0165] Prepare high flash point aromatic hydrocarbons;

[0166] High flash point aromatic hydrocarbon solvent, purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd., S150 solvent oil.

[0167] The scale dissolving performance of high flash point aromatic hydrocarbon solvent was tested in the same manner as in Example 1. After testing, the asphalt dissolving rate was 100%, inorganic scale and clay minerals could not be dissolved, and polymer micelles could not be degraded. The dissolution rate of the 1# mixed plugging sample was 32%; the dissolution rate of the 2# mixed plugging sample was 26%; the dissolution rates of the two mixed scales were low.

[0168] Comparative Example 2: 15% hydrochloric acid system

[0169] Prepare 15% hydrochloric acid system, 15% HCL + 1% corrosion inhibitor + 1% iron stabilizer + 1% drainage aid + 1% demulsifier + balance water.

[0170] HCL is 31% industrial hydrochloric acid, purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.; the corrosion inhibitor is an imidazoline corrosion inhibitor, purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.; the iron stabilizer is citric acid, purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.; the drainage agent is a fluorocarbon surfactant (C8F 17 SO2NHC3H7NR2(O)), purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.; demulsifier is nonylphenol polyoxyethylene ether (C 15 H 24 O(C2H4O) n ), purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.

[0171] The scale dissolving performance of the hydrochloric acid system was tested in the same manner as in Example 1. After testing, the calcium carbonate dissolving rate was 100%, the magnesium carbonate dissolving rate was 100%, the iron hydroxide dissolving rate was 100%, barium sulfate, strontium sulfate and asphalt were not dissolve, and the polymer micelles were not degraded. The dissolution rate of the 1# mixed plugging sample was 42%; the dissolution rate of the 2# mixed plugging sample was 35%; the dissolution rates of the two mixed scales were low.

[0172] Comparative Example 3: Ammonium Persulfate

[0173] A 2% ammonium persulfate solution was prepared, wherein the ammonium persulfate was purchased from Tianjin Development Zone Kuayue Industry and Trade Co., Ltd.

[0174] The scale dissolving performance of ammonium persulfate was tested in the same manner as in Example 1. The test showed that the polymer micelles of the 1# mixed plugging sample could be partially degraded, the viscosity reduction rate was 52%, and there was no scale dissolving ability; and there was no dissolving ability for the 2# mixed plugging sample.

[0175] The present invention has been disclosed above with preferred embodiments, but those skilled in the art should understand that these embodiments are only used to describe the present invention and should not be understood as limiting the scope of the present invention. It should be noted that all changes and substitutions equivalent to these embodiments should be deemed to be included in the scope of the claims of the present invention. Therefore, the scope of protection of the present invention should be based on the scope defined in the claims.

Claims

1. A nano-chelating plugging remover, characterized in that: Calculated by weight percentage, the invention comprises: 60%-95% of a chelating agent-containing water phase, 0.1%-10% of an oil phase, 0.1%-20% of a surfactant and 0.1%-10% of an auxiliary surfactant.

2. The nano-chelating plugging remover according to claim 1, characterized in that: Calculated by weight percentage, the invention comprises: 80%-90% of a chelating agent-containing water phase, 1%-4% of an oil phase, 6%-10% of a surfactant and 3%-6% of an auxiliary surfactant.

3. The nano-chelating plugging remover according to claim 1, characterized in that: Calculated by weight percentage, the composition comprises: 86% of a chelating agent-containing water phase, 2% of an oil phase, 8% of a surfactant and 4% of an auxiliary surfactant.

4. The nano-chelating plugging remover according to claim 1, characterized in that: The chelating agent-containing aqueous phase comprises a chelating agent, a demulsifier and water in a weight ratio of (10-30): (0.1-2.0): (59-89.9).

5. The nano-chelating plugging remover according to claim 4, characterized in that: The chelating agent is selected from two or more of sodium citrate, trisodium nitrilotriacetate, trisodium hydroxyethylethylenediaminetriacetate, disodium ethylenediaminetetraacetate, tetrasodium ethylenediaminetetraacetate, tetrasodium aminotrimethylene phosphate, tetrasodium hydroxyethylidene diphosphate, pentasodium diethylenetriaminepentamethylenediphosphate, pentasodium diethylenetriaminepentaacetate and tetrasodium glutamate diacetate; the demulsifier is selected from one or more of sodium dioctyl diacid sulfonate, polyoxyethylene ether, phenolamine resin polyether, phenolic resin polyether and polyacrylate.

6. The nano-chelating plugging remover according to claim 1, characterized in that: The oil phase is selected from one or more of n-hexane, cyclohexane, limonene, and high flash point heavy aromatic hydrocarbons.

7. The nano-chelating plugging remover according to claim 1, characterized in that: The surfactant is one or more of dodecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium bromide, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium bromide, hexadecyltrimethylammonium chloride, fatty alcohol polyoxyethylene ether, sodium lauryl sulfate, and styrylphenol polyoxyethylene ether.

8. The nano-chelating plugging remover according to claim 1, characterized in that: The co-surfactant is one or more of isopropanol, n-butanol, n-pentanol, n-hexanol, ethylene glycol, and propylene glycol.

9. The method for preparing the nano-chelating plugging remover according to any one of claims 1 to 8, characterized in that: include: The chelating agent-containing water phase, oil phase, surfactant and co-surfactant are mixed in proportion, and stirred at 0-50° C. for 0.5-2 hours to obtain the nano-chelating plugging remover.

10. The method for using the nano-chelating plugging remover according to any one of claims 1 to 8, characterized in that: include: (1) Injecting nano-chelated plugging remover into the well; (2) injecting displacement fluid; (3) After shutting in the well for 6-48 hours, the oil well is put into production / the water well is put into operation.

11. The method for using the nano-chelating plugging remover according to claim 10, characterized in that: In step (1), the displacement of the nano-chelating plugging remover is 0.1-1.5m 3 / min; in step (2), the displacement of the displacement fluid is 0.1-1.5m 3 / min.

12. Use of the nano-chelated plugging remover according to any one of claims 1 to 8 in the development and exploitation of sandstone and carbonate oil and gas reservoirs.

Citation Information

Patent Citations

  • A kind of descaling and blocking agent and preparation method thereof

    CN117511527B

  • Oilfield blocking remover and blocking removal method

    CN117683524A

  • Novel calcium carbonate scale and barium sulfate scale blocking-removing chelating scale remover and preparation method thereof

    CN117735737A